2008
DOI: 10.1080/17453670710014806
|View full text |Cite
|
Sign up to set email alerts
|

Forearm bone-anchored amputation prosthesis: A case study on the osseointegration

Abstract: Background and purpose Bone-anchored titanium implants have been used for anchorage of amputation prostheses for more than one and a half decades. Histological and ultrastructural analyses were performed on a forearm amputation prosthesis after being in use for more than 11 years.Material, methods and results The implant was retrieved from the ulnar bone after a fatigue fracture of the titanium implant, and was clinically stable at the time of removal. The histological findings showed a large amount of bone wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 14 publications
2
34
0
Order By: Relevance
“…It has been postulated that the difficulties associated with FIB techniques on smoother implant interfaces is probably partly due to volume reduction of the tissue, related to fixation and dehydration, and partly due to minimal biomechanical integration needed to withstand tensions at the immediate interface. However, a small amount of biological tissue is always present at the immediate interface of FIB-produced specimens [5,13], confirming a preparation artefact rather than a lack of osseointegration on the nano-level. For the laser-modified surface, intact samples could be readily prepared by FIB, and showed an intimate contact between the surface oxide and bone tissue using TEM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the difficulties associated with FIB techniques on smoother implant interfaces is probably partly due to volume reduction of the tissue, related to fixation and dehydration, and partly due to minimal biomechanical integration needed to withstand tensions at the immediate interface. However, a small amount of biological tissue is always present at the immediate interface of FIB-produced specimens [5,13], confirming a preparation artefact rather than a lack of osseointegration on the nano-level. For the laser-modified surface, intact samples could be readily prepared by FIB, and showed an intimate contact between the surface oxide and bone tissue using TEM.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this perception might be true in the short term. Long-term effects must be considered, since DSA is intended for lifelong use and present reports on the long-term applications of the DSA are still limited [86]. …”
Section: Bone-implant Interfacementioning
confidence: 99%
“…The structure of the intact bone/titanium interface is now well characterized down to the nanoscale (Palmquist et al 2008(Palmquist et al , 2009(Palmquist et al , 2010. However, the early cellular and molecular activities determining the early tissue response and bone formation at the bone/ implant interface are not yet fully understood.…”
Section: Cell and Molecular Biologymentioning
confidence: 99%
“…These interposed layers could either be electron dense (Steflik et al 1999) or electron lucent (Albrektsson et al 1985) and sometimes referred to as a cement-like line (Davies 2007). With the use of FIB for sample preparation where an intact interface could be analysed as both implant and tissue are present in the sample, it has recently been shown that the interface is mineralized both for machined (Palmquist et al 2008) and laser modified implants (Palmquist et al 2010). Further, it has also been demonstrated that the bonding mechanisms are different between different implant surfaces where micro-and nanostructured laser-modified implant surfaces attain a strong bonding at the nano-level (figure 3).…”
Section: Ultrastructurementioning
confidence: 99%